Improved Insurance Coverage Increased Biosimilar Semglee's Market Share After The FDA's Interchangeability Designation - Kakani, Pragya; Katcher, Bradley A; Maini, Luca (Health affairs (Millwood, Va.), 2025)
Interchangeability, a Food and Drug Administration (FDA) designation allowing pharmacists to substitute a biosimilar for its branded originator at the point of sale, is intended to increase biosimilar adoption. However, little is known about the relationship between interchangeability and biosimilar adoption. We conducted an interrupted time-series analysis to examine this relationship for Semglee, which gained interchangeability in July 2021, in Medicaid and the employer-sponsored insurance market in 2021-22. Semglee is a biosimilar for Lantus (insulin glargine), the most-prescribed long-acting insulin in the US. We found that Semglee market share increased by 3.70 percentage points in Medicaid and 19.25 percentage points in employer-sponsored insurance beginning in the first quarter of 2022, coinciding with improved Semglee coverage, especially in employer-sponsored insurance. State-level variation in pharmacist substitution laws was not associated with Semglee adoption. These results suggest that increased adoption was mediated mainly through improved insurance coverage, with no detectable role for increased prescribing alone and only a secondary role, at most, for pharmacist substitution. Semglee's gains in market share after interchangeability suggest that easing of federal interchangeability requirements may moderately spur biosimilar adoption.